Comparison of effectiveness disinfection of 2% glutaraldehyde and 4.8% chloroxylenol on tooth extraction instruments in the Department of Oral Maxillofacial and Surgery, Faculty of Dentistry, University of North Sumatera - Ahyar Riza; Indra B. Siregar; Isnandar Isnandar; Bernard Bernard (DiscoverSys Inc., 2018)
Objective: To compare disinfecting effectiveness of 2% glutaraldehyde and 4.8% chloroxylenol on tooth extraction instruments at the Department of Oral Surgery, Faculty of Dentistry, Universitas Sumatera Utara.Material and Methods: This was an experimental study with post-test only control group design approach. Purposive technique is applied to collect samples which are lower molar extraction forceps. In this study, sample were divided into 2 groups and each consisting of 18 instruments. The treatment group was treated with 2% glutaraldehyde while the control group was treated with 4.8% chloroxylenol. Each instrument was pre-cleaned using a brush, water and soap for both groups underwent the disinfection process.Results: The results were statistically analyzed using Mann-Whitney Test. The comparison between glutaraldehyde and chloroxylenol showed a significant difference to the total bacteria count on instrument after disinfection (p=0.014 < 0.05).Conclusion: 2% glutaraldehyde was more effective than 4.8% chloroxylenol at disinfecting lower molar extraction forceps.